Treatment Outcomes of Nilotinib as Second Line Therapy for Chronic Myeloid Leukemia Patients in Karbala Province of Iraq - Mjali, Ahmed; Obaid, Mustafa Majeed; Matti, Bassam Francis; Abbas, Nareen Tawfeeq (Asian Pacific Journal of Cancer Care, 2022)
Background: Second line treatment of chronic myeloid leukemia (CML) is crucial after imatinib therapy failure. In Iraq, nilotinib is the only available second line tyrosine kinase inhibitors (TKIs), making management of CML patients with failure response to 1st generation TKIs as a great challenge to the health system. Objectives: Our study tries to evaluate nilotinib safety and efficacy among CML patients in Karbala province of Iraq as the only drug available as second line treatment for CML patients post imatinib failure. Materials & Methods: This research was carried out in Al-Hussein cancer center in Karbala province of Iraq between January 2012 & December 2020. Nilotinib was used as a second-line treatment for 30 CML patients and their response were assessed by the level of BCR-ABL1 transcription in peripheral blood at 3 months, 6 months and 12 months from starting treatments. Results: The median age was 42.5 years, included 16 males and 14 females with male to female ratio 1.14. According to Sokal score 15 patients were high risk, 11 patients were intermediate risk and 4 patients were low risk. More than 66% of our patients achieved major molecular response (MMR) after starting nilotinib as second line. The BCR- ABL transcription level had a significant reduction from baseline at 3 months, 6 months and 12 months respectively (P value <0.05). Male patients and those who received imatinib for ≥ 24 months were better survival. Conclusion: Nilotinib is effective and safe drugs as second line treatment among Iraqi patients.